HABITUASI PADA RUSA TOTOL (Axis axis Erxleben, 1777) DI PENANGKARAN DENGAN PANGGILAN, WARNA PAKAIAN DAN URIN (Habituation of Axis Deer – Axis axis Erxleben, 1777 in Captive Breeding by Calling, Clothes Colour and Urine) - . Sukriyadi; Machmud Thohari; Burhanuddin Masyud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
The experiment was carried out to study habituation of axis deer in captive by calling, urine and clothes colour. Fifteen individuals of axis deer (7 males and 8 females) were used to test the effect of calling, urine and clothes color to adaptation and habituation of deer, using factorial with simple ramdom design. Four colorurs of keeper wear were tested in this experiment i.e. green, red, black and yellow. Calling treatment was conduted by keeper sound using tape recorder. To test the effect of urine was conducted by adding feed with the keepr’s urine. The deers was classified into two age groups (adult, sub adult and adolescent) and sex (male and female). Distance between deer to keeper was used to determine the effect of treatment. Result of research showed that deers were positive response to the calling, colour of clothes and urine adding in the food by moving to near the keeper. Red colour of clothes were better response than the others. According to the age-classes of deer, research showed that adult female deers were faster adapt than the others. In conclusion, treatment by using calling (sound), red colour of clothes and added of urine into deer’s food were positive to faster of adaptation and habituation process of deers in captivity.Key words: habituation, Axis axis, calling, urine, colour.